PEMBUATAN LKPD BERORIENTASI KOMPLEKSITAS KONTEN DAN PROSES KOGNITIF PADA MATERI SUHU DAN KALOR UNTUK PEMBELAJARAN FISIKA SMA/ MA - Ahmad Fajrin; Amali Putra; Letmi Dwiridal (Universitas Negeri Padang, 2017)
This research is motivated by the non-optimal achievement of competence of learners to physics. To improve the competence of learners, developed teaching material in sheet form K0erja Students (LKPD) Complexity Oriented Content and Cognitive Processes.This study included research into the types of development (research and development). The development model used is the model 4-D comprising the step of defining (define), design (design), development (development), and the spread (disseminate). LKPD trials conducted prior to 5 people validator. Furthermore LKPD tested the practicality of the two teachers and a large number of learners. The final stage of this study is testing the effectiveness is limited to a number of learners.Validity test results obtained LKPD overall average value of 3.00, test the practicalities of teachers SMAN 4 Padang obtained an average value of 3.37 as well as the practicalities of test results obtained learners speserta average value of 3.37. Based on these results, we can conclude that Complexity Content Student and Cognitive Process Worksheet generated in the category valid and practical. While the effectiveness of the test results obtained by value Student Worksheet gain a score of 0.47, meaning that the researchers developed of Student Worksheet that are in the moderate category and can be used to improve the competence of learners